New Fractional Spline Polynomial for Computing Fractional Differential Equations (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This paper illustrates how fractional lacunary for quartic polynomial using spline function has been constructed.  On the other hand the existence, the uniqueness and error bounded for these functions have been discussed and proved. The goal of this method is to solve fractional differential equations. The efficiency and pertinence of these new methods are illustrated by giving numerically computing examples.